Acute Purulent Keratitis of Mixed Etiology Developed during Contact Lens Wearing. Clinical Case - Evg. A. Kasparova; N. R. Marchenko; M. N. Narbut; Z. V. Surnina; D. A. Krivolapova (Oftalʹmologiâ, 2023)
The article presents a description of a clinical case of advanced purulent keratitis of mixed etiology (Pseudomonas aeruginosa + acanthamoeba),  developed as a result of a mode violation of soft contact lens wearing.  Confocal microscopy of the cornea revealed multiple rounded hyperreflective formations (acanthamoeba cysts). Complex anti-infective conservative therapy in combination with modified crosslinking stops rapidly progressing purulent keratitis and increases visual acuity from 0.01 to 0.9.